Chromosomal Microarray Analysis in Pregnancies With Corpus Callosum or Posterior Fossa Anomalies. (June 2021) - Greenbaum, Lior; Maya, Idit; Sagi-Dain, Lena; Sukenik-Halevy, Rivka; Berkenstadt, Michal; Yonath, Hagith; Rienstein, Shlomit; Shalata, Adel; Katorza, Eldad; Singer, Amihood
Abstract : Objective: We investigated the detection rate of clinically significant chromosomal microarray analysis (CMA) results in pregnancies with sonographic diagnosis of fetal corpus callosum anomalies (CCA) or posterior fossa anomalies (PFA). Methods: All CMA tests in pregnancies with CCA or PFA performed between January 2015 and June 2020 were retrospectively evaluated from the Israeli Ministry of Health database. The rate of CMA with clinically significant (pathogenic or likely pathogenic) findings was calculated and compared to a local Israeli cohort of 5, 541 pregnancies with normal ultrasound. Results: One hundred eighty-two pregnancies were enrolled: 102 cases with CCA and 89 with PFA (9 cases had both). Clinically significant CMA results were found in 7/102 of CCA (6.9%) and in 7/89 of PFA (7.9%) cases. The CMA detection rate in pregnancies with isolated CCA (2/57, 3.5%) or PFA (2/50, 4.0%) was lower than in nonisolated cases, including additional CNS and/or extra-CNS sonographic anomalies (CCA-5/45, 11.1%; PFA-5/39, 12.8%), but this was not statistically significant. However, the rate among pregnancies that had extra-CNS anomalies, with or without additional CNS involvement (CCA-5/24, 20.8%; PFA-5/29, 17.2%), was significantly higher compared to all other cases ( p = 0.0075 for CCA; p = 0.035 for PFA). Risk of CMA with clinically significant results for all and nonisolated CCA or PFA pregnancies was higher compared to the background risk reported in the control cohort ( p < 0.001), but was not significant for isolated cases. Conclusions: Our findings suggest that CMA testing is beneficial for the genetic workup of pregnancies with CCA or PFA, and is probably most informative when additional extra-CNS anomalies are observed.